Legal Consequences Of Insider Trading In Limited Liability Companies - yeni triana (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
The background of this study focuses on insider trading practices and the legal consequences for insider trading perpetrators in limited liability companies. The specific target of this study is to explain the legal consequences for insider trading perpetrators. The insider trading phenomenon is pivotal to examining the limited liability companies' evolution, as insider trading may impact the company's prospects. Insider Trading provides many benefits for its perpetrators, including obtaining accurate information from insiders regarding the company's prospects in the future. This information can augment stock prices and can also decrease significantly. It allows the perpetrators to gain extraordinary profits by buying or selling earlier than other parties. Through insider trading, investors can earn profits that other parties may not enjoy. Indonesia classifies insider trading as a crime. This point is in line with Law Number 8 of 1995 regarding the Capital Market, which prohibits individuals possessing insider information about a company from purchasing or selling shares in the capital market.